GY MEDIC : Analysis and rehabilitation system for patients with facial paralysis. - Guanoluisa Panchi, Gissela Maricruz (2019)
The diagnosis and treatment of facial paralysis is timely in the first seventy-two hours to avoid implications on the return of motor functions of facial muscles. The proposed solution is a software made up of two modules for the analysis and rehabilitation of facial paralysis: (i) The analysis module detects and quantifies the level of asymmetry in the face, this is achieved with the inclusion of techniques for calculating the divergence between the vital points of the face located in the eyes, nose and mouth, measurements optimized with the gamma correction method; (ii) The rehabilitation module stimulates the facial nerves with physical exercises and monitors the patient’s progress during therapy, for this purpose, a 3D virtual environment was developed that tracks the patient’s facial gestures and, through these, directs a series of activities supported in the physical rehabilitation processes.